2019
DOI: 10.3390/w11112301
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Forest Thinning on the Long-Term Runoff Changes of Coniferous Forest Plantation

Abstract: Forests and water are closely related to each other. Thus, forest management is crucial for the sustainable clean water supply. Forest thinning is one of the fundamental forest management practices, as it can change runoff by controlling the density of trees. In this study, the effect of forest thinning on long-term runoff changes was evaluated, based on the long-term rainfall-runoff data of a coniferous plantation forest catchment in Korea. From the double mass curve and Pettitt’s test, a statistically signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Using this method and change-point analysis, runoff data were separated into the baseline period and the variation period. It was widely used to estimate the impact of human activities [21,[75][76][77][78]. In this study, by substituting the rainfall accumulation data in the post-mutation period into the equation of the rainfall-runoff double accumulation curve prior to the mutation, we obtained a set of runoff data that differed from the original post-mutation runoff data.…”
Section: Runoff Variation and Attribution Analysis Methodsmentioning
confidence: 99%
“…Using this method and change-point analysis, runoff data were separated into the baseline period and the variation period. It was widely used to estimate the impact of human activities [21,[75][76][77][78]. In this study, by substituting the rainfall accumulation data in the post-mutation period into the equation of the rainfall-runoff double accumulation curve prior to the mutation, we obtained a set of runoff data that differed from the original post-mutation runoff data.…”
Section: Runoff Variation and Attribution Analysis Methodsmentioning
confidence: 99%
“…Thinning alters the hydrological components of the canopy and understory vegetation affecting runoff (e.g., Dung et al, 2012; Kuraji et al, 2019; Yang, 2019). Sun et al (2017) showed that evapotranspiration decreased by 21.4% after 50% strip‐thinning by plot scale measurements, while annual interception and transpiration decreased from 414.8 to 263.0 mm and from 441.0 to 272.1 mm, respectively.…”
Section: Introductionmentioning
confidence: 99%